Anode and secondary battery including said anode

The use of a binder comprising a (meth)acrylamide group-containing monomer, unsaturated carboxylic acid monomer, and cellulose nanofibers in the negative electrode active material layer addresses the detachment and conductive path issues of silicon-based particles, enhancing battery durability and capacity retention.

JP2025500323AActive Publication Date: 2025-01-09LG ENERGY SOLUTION LTD

Patent Information

Application Number
JP2024537147
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-24
Filing Date
2022-09-21
Publication Date
2025-01-09
Estimated Expiration
2042-09-21

AI Technical Summary

Technical Problem

Silicon-based particles in negative electrodes of secondary batteries experience detachment and reduced conductive paths due to large volume changes during charging and discharging, leading to shortened battery life, particularly when using high molecular weight acrylic binders that hinder slurry dispersion and increase brittleness.

Method used

A negative electrode active material layer using a binder composed of a (meth)acrylamide group-containing monomer, unsaturated carboxylic acid monomer, and monomers with low water solubility, combined with cellulose nanofibers, enhances adhesive strength and maintains conductive paths despite volume changes.

Benefits of technology

The combination improves the durability and adhesive strength of the negative electrode, preventing detachment and maintaining conductive paths, thereby extending battery life and capacity retention.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025500323000001_ABST
    Figure 2025500323000001_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode and a secondary battery, the negative electrode active material layer including a negative electrode active material layer including a negative electrode active material and a binder, the binder including: a) an acrylic polymer that is a polymer of a monomer mixture including a (meth)acrylamide group-containing monomer, an unsaturated carboxylic acid monomer, and a monomer having a solubility in water of 100 g / L or less; and b) cellulose nanofibers.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0187721, filed December 24, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.

[0002] The present invention relates to a negative electrode including a negative electrode active material layer, the negative electrode active material layer including a negative electrode active material and a binder, the binder including: a) an acrylic polymer that is a polymer of a monomer mixture including a (meth)acrylamide group-containing monomer, an unsaturated carboxylic acid monomer, and a monomer having a solubility in water of 100 g / L or less; and b) cellulose nanofibers; and a secondary battery including the negative electrode. [Background technology]

[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy, and one of the most actively researched fields in this area is the field of power generation and storage using electrochemical reactions.

[0004] At present, a representative example of such electrochemical elements using electrochemical energy is a secondary battery, and the range of its use is expanding. Recently, with the development of technology and increasing demand for portable devices such as portable computers, mobile phones, and cameras, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, much research has been conducted on high energy density, i.e., high capacity lithium secondary batteries, which have been commercialized and are widely used.

[0005] In general, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material that inserts and removes lithium ions from the positive electrode. Silicon-based particles having a large discharge capacity can be used as the negative electrode active material.

[0006] However, silicon-based particles have low initial efficiency and undergo excessive volume change during charging and discharging. As a result, when the battery is operated, the silicon-based particles may detach from the negative electrode or the conductive path in the negative electrode may decrease, resulting in a shortened battery life. In particular, when so-called pure silicon silicon particles (particles made of silicon) are used, the above problems become more pronounced.

[0007] In order to prevent the silicon-based particles from detaching even when the silicon-based particles undergo large volume changes and to maintain the conductive path, there have been attempts to improve the binder. For example, a technique has been attempted in which an acrylic binder is used instead of the combined use of carboxymethyl cellulose and styrene-butadiene rubber.

[0008] In order to prevent the silicon particles from detaching while using an acrylic binder and maintain the conductive path to improve the battery life, the acrylic binder has been adjusted to have a high modulus. For example, the weight average molecular weight of the acrylic binder is as high as 400,000 or more, and the T g However, if the weight average molecular weight of the acrylic binder is high, it is difficult to disperse the negative electrode slurry, which reduces the conductivity in the negative electrode. g If the value is too high, the brittleness of the negative electrode active material layer increases excessively, and the adhesive strength of the negative electrode decreases. For this reason, the weight average molecular weight and T g It is necessary to move away from the traditional method of adjusting values. Therefore, new technologies that can improve the life characteristics of batteries are required. Summary of the Invention [Problem to be solved by the invention]

[0009] One problem to be solved by the present invention is to provide a negative electrode having improved battery life characteristics. Another problem to be solved by the present invention is to provide a secondary battery including the negative electrode. [Means for solving the problem]

[0010] According to one embodiment of the present invention, there is provided a negative electrode comprising a negative electrode active material layer, the negative electrode active material layer comprising a negative electrode active material and a binder, the binder comprising: a) an acrylic polymer which is a polymer of a monomer mixture including a (meth)acrylamide group-containing monomer, an unsaturated carboxylic acid monomer, and a monomer having a solubility in water of 100 g / L or less; and b) cellulose nanofibers. According to another embodiment of the present invention, there is provided a secondary battery including the negative electrode. Effect of the Invention

[0011] According to the present invention, the acrylic polymer can be uniformly dispersed in the negative electrode slurry, and the cellulose nanofiber can act as a filler in the negative electrode active material layer, thereby improving the durability of the negative electrode.

[0012] In addition, the carboxy group on the surface of the cellulose nanofiber is bonded to the hydroxyl group of the acrylic polymer, so that the tensile strength of the binder can be at a high level. As a result, the structure of the negative electrode can be maintained even when the negative electrode active material, especially the silicon particles, undergoes a sudden volume change, the detachment of the negative electrode active material can be suppressed, and the conductive path can be effectively maintained in the negative electrode active material layer. As a result, the life characteristics of the battery can be improved.

[0013] Furthermore, since the cellulose nanofibers are longer than the conventionally used carboxymethyl cellulose, they can be easily adsorbed to the negative electrode active material. Unlike styrene butadiene rubber, the cellulose nanofibers can be surface-adhered to surrounding components, which can further improve the adhesive strength of the negative electrode and prevent detachment of the negative electrode active material during battery operation, thereby further improving the battery life. [Brief description of the drawings]

[0014] [Figure 1] 1 is a graph showing the capacity retention rates of secondary batteries using the negative electrodes of Examples 1 to 6 and Comparative Examples 1 and 2 at room temperature. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention will now be described in more detail to aid in understanding the invention. The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0016] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. The singular expressions include the plural expressions unless otherwise clearly indicated in the context.

[0017] It should be understood that, as used herein, terms such as "comprises," "comprising," or "having" are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, but do not preclude the presence or additional possibility of one or more other features, numbers, steps, components, or combinations thereof.

[0018] In this specification, D 50 can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve. 50 can be measured by using, for example, a laser diffraction method. The laser diffraction method generally allows measurement of particle sizes from the submicron range to about several mm, and can provide results with high reproducibility and high resolution.

[0019] In this specification, "weight average molecular weight (Mw)" means a value converted to standard polystyrene measured by gel permeation chromatography (GPC). Specifically, the weight average molecular weight is a value converted from a value measured under the following conditions using GPC, and standard polystyrene from an Agilent system was used to create a calibration curve.

[0020] <Measurement conditions> Measuring instrument: Ultrahydrogel Linear x 2 Solvent: 0.1M NaNO3, pH7 phosphate buffer (0.45μm filtered) Flow rate: 1.0ml / min Sample concentration: 1.0mg / ml Injection volume: 100μl Column temperature: 40℃ Detector: Waters RI detector Standard sample: Polyacrylic acid (corrected by a cubic function) Data Processing: Empower 3

[0021] In this specification, the "specific surface area" is measured by the BET method, and specifically, it can be calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mino II manufactured by BEL Japan.

[0022] In this specification, the modulus can be measured by the following method. The polymer solution was dried at room temperature to prepare a film, which was then punched out into a sample size of 10mm x 20mm. The modulus was confirmed by measuring the strain-stress at a strain rate of 5mm / min using a Text Analyzer.

[0023] <Negative electrode> A negative electrode according to one embodiment of the present invention includes a negative electrode active material layer, and the negative electrode active material layer includes a negative electrode active material and a binder. The binder may include: a) an acrylic polymer that is a polymer of a monomer mixture including a (meth)acrylamide group-containing monomer, an unsaturated carboxylic acid monomer, and a monomer having a solubility in water of 100 g / L or less; and b) cellulose nanofibers.

[0024] The negative electrode may include a negative electrode active material layer. The negative electrode active material layer may be disposed on a negative electrode current collector. The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity. For example, the current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, or the like. Specifically, a transition metal that easily adsorbs carbon, such as copper or nickel, may be used as the negative electrode current collector. The thickness of the negative electrode current collector may be 6 μm to 20 μm, but the thickness of the negative electrode current collector is not limited thereto. The negative electrode active material layer may be disposed on one or both sides of the current collector. The negative electrode active material layer may include a negative electrode active material and a binder.

[0025] 1.Negative electrode active material The negative electrode active material may include a silicon-based active material, which enables the negative electrode to have a high capacity.

[0026] In particular, the negative electrode active material may include silicon particles. The silicon particles may be silicon particles (particles made of silicon) called pure silicon. The silicon particles can effectively improve the capacity of the negative electrode. The silicon particles may rapidly change in volume during the charging and discharging process of the battery, which may reduce the life characteristics of the negative electrode. However, in the present invention, since the binder contains an acrylic polymer containing an acrylamide-derived unit and cellulose nanofibers, the silicon particles can be prevented from being detached even when the silicon particles rapidly change in volume, and the conductive path in the negative electrode active material layer can be maintained, thereby improving the life characteristics of the negative electrode.

[0027] The average particle size of the silicon particles (D 50 ) may be 1 μm to 10 μm, specifically, 3 μm to 5 μm. The silicon particles may be contained in the negative electrode active material layer in an amount of 75 to 85% by weight. When this range is satisfied, the capacity of the negative electrode can be effectively improved.

[0028] 2. Binder The binder may include: a) an acrylic polymer that is a polymer of a monomer mixture containing a (meth)acrylamide group-containing monomer, an unsaturated carboxylic acid monomer, and a monomer having a solubility in water of 100 g / L or less; and b) cellulose nanofibers.

[0029] (1) Acrylic polymer The acrylic polymer may act as a binder and a thickener in the negative electrode active material layer.

[0030] The acrylic polymer may be a polymer of a monomer mixture containing (a1) a (meth)acrylamide group-containing monomer, (a2) an unsaturated carboxylic acid monomer, and (a3) ​​a monomer having a solubility in water of 100 g / L or less.

[0031] The (meth)acrylamide group-containing monomer may be, for example, one or more monomers selected from the group consisting of acrylamide, N-methylolacrylamide, N-butoxymethylacrylamide, N-methylolmethacrylamide, N-butoxymethylmethacrylamide, N,N-diethylacrylamide, N,N-dimethylacrylamide, N,N-diethylmethacrylamide, N-ethylacrylamide, N-propylacrylamide, and N-tert-butylacrylamide, used alone or in combination, but is not limited thereto.Specifically, the (meth)acrylamide group-containing monomer may be acrylamide.

[0032] The (meth)acrylamide group-containing monomer may be included in an amount of 60 to 90 parts by weight, specifically 70 to 85 parts by weight, based on 100 parts by weight of the monomer mixture. When the content of the (meth)acrylamide group-containing monomer is within this range, the adhesive strength of the negative electrode may be improved, detachment of the negative electrode active material may be suppressed, and the durability of the negative electrode may be improved.

[0033] The unsaturated carboxylic acid monomer may be, for example, one or more selected from the group consisting of acrylic acid, methacrylic acid, crotonic acid, isocrotonic acid, maleic anhydride, fumaric acid, and itaconic acid, used alone or in combination, but is not limited thereto.Specifically, the unsaturated carboxylic acid monomer may be acrylic acid.

[0034] The unsaturated carboxylic acid monomer may be included in an amount of 8 parts by weight to 30 parts by weight, specifically 10 parts by weight to 25 parts by weight, based on 100 parts by weight of the monomer mixture. When the content of the unsaturated carboxylic acid monomer satisfies the above range, the negative electrode active material and the conductive material can be effectively dispersed, and the adhesive strength between the negative electrode current collector and the negative electrode active material can be sufficiently secured.

[0035] The monomer having a solubility in water of 100 g / L or less means a monomer that dissolves in an amount of 100 g or less when added to 1 L of water at 25° C. When the acrylic polymer contains a monomer having such low solubility in water, it is possible to obtain an effect of reducing the water content in the negative electrode.

[0036] The monomer having a solubility in water of 100 g / L or less may be, for example, one or more monomers selected from the group consisting of alkyl (meth)acrylates having 1 to 10 carbon atoms, (meth)acrylonitrile, and styrene, but is not limited thereto.

[0037] Specific examples of the alkyl (meth)acrylate having 1 to 10 carbon atoms include, but are not limited to, methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, n-amyl acrylate, isoamyl acrylate, n-ethylhexyl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, n-ethylhexyl methacrylate, 2-ethylhexyl methacrylate, etc. Specific examples of the (meth)acrylonitrile include acrylonitrile and methacrylonitrile.

[0038] The monomer having a solubility in water of 100 g / L or less may be included in an amount of 2 parts by weight to 10 parts by weight, specifically 4 parts by weight to 8 parts by weight, based on 100 parts by weight of the monomer mixture. When the content of the monomer having a solubility in water of 100 g / L or less satisfies the above range, an acrylic polymer that is easily dissolved in water can be obtained while reducing the water content in the negative electrode.

[0039] The glass transition temperature (T g) may be 100° C. to 150° C., specifically 110° C. to 140° C., and more specifically 120° C. to 130° C. When the above range is satisfied, the processability during the production of the negative electrode can be improved, and the adhesive strength of the negative electrode can be improved.

[0040] The acrylic polymer may be contained in the negative electrode active material layer in an amount of 1 wt% to 30 wt%, specifically 3 wt% to 20 wt%, more specifically 5 wt% to 15 wt%, for example 1 wt% to 9.5 wt%. When the range is satisfied, detachment of the negative electrode active material is effectively suppressed, and the battery life can be further improved.

[0041] The acrylic polymer can be produced by mixing the monomer components to form a monomer mixture, and then polymerizing the monomer mixture. In this case, the polymerization may be carried out using a normal polymerization method well known in the art, such as a solution polymerization method or an emulsion polymerization method, and the polymerization temperature and polymerization time may be appropriately determined depending on the polymerization method, the type of polymerization initiator, and the like. For example, the polymerization temperature may be 50°C to 100°C, and the polymerization time may be 1 to 10 hours. In addition, during the polymerization, a polymerization initiator, a molecular weight regulator, and the like may be further added as necessary. As the polymerization initiator, an inorganic or organic peroxide may be used, and for example, a water-soluble initiator including potassium persulfate, sodium persulfate, ammonium persulfate, and the like may be used. As the molecular weight regulator, for example, mercaptans or terpenes such as terpinolene, dipentene, and t-terpinene, and halogenated hydrocarbons such as chloroform and carbon tetrachloride may be used.

[0042] (2) Cellulose nanofiber The cellulose nanofibers, when used in combination with the acrylic binder, improve the toughness of the binder. As a result, even if the negative active material (especially silicon particles) undergoes excessive volumetric change during charging and discharging of the battery, the negative active material can be prevented from being detached from the negative active material layer, and the conductive path of the negative active material layer can be maintained. As a result, the life characteristics of the battery using the negative electrode can be improved.

[0043] In particular, the cellulose nanofibers are highly effective when used in combination with the acrylic polymer. When the negative electrode active material layer uses only an acrylic polymer as a binder, the acrylic polymer is a linear or partially branched polymer, so that it is difficult to prevent the structural collapse of the negative electrode when the negative electrode active material undergoes excessive volume change, and the adhesive strength of the negative electrode is low.

[0044] In contrast, when the negative electrode active material layer contains an acrylic polymer and cellulose nanofibers as a binder, the acrylic polymer can be uniformly dispersed in the negative electrode active material layer, and the cellulose nanofibers can act as a filler in the negative electrode active material layer, thereby improving the durability of the negative electrode.

[0045] In addition, the carboxy group on the surface of the cellulose nanofiber is bonded to the hydroxyl group of the acrylic polymer, so that the tensile strength of the binder can be at a high level. As a result, the structure of the negative electrode can be maintained even when the negative electrode active material, especially the silicon particles, undergoes a sudden volume change, the detachment of the negative electrode active material can be suppressed, and the conductive path can be effectively maintained in the negative electrode active material layer. As a result, the life characteristics of the battery can be improved.

[0046] Furthermore, since the cellulose nanofibers are longer than the conventionally used carboxymethyl cellulose, they can be easily adsorbed onto the negative electrode active material, and unlike styrene-butadiene rubber, they can be surface-adhered to the surrounding components, which can further improve the adhesive strength of the negative electrode.

[0047] The material of the cellulose nanofiber may be formed from a polysaccharide having a β-1,4-glucan structure. Examples of the cellulose nanofiber include cellulose nanofibers derived from higher plants (e.g., natural cellulose fibers (pulp fibers) such as wood fibers (wood pulp from conifers, broad-leaved trees, etc.), bamboo fibers, sugarcane fibers, seed hair fibers (e.g., cotton linters, bombax cotton, kapok, etc.), bast fibers (e.g., hemp, paper mulberry, Mitsumata, etc.), and leaf fibers (e.g., Manila hemp, New Zealand hemp, etc.)), animal-derived cellulose fibers (e.g., sea squirt cellulose), bacterial-derived cellulose fibers (e.g., cellulose contained in nata de coco), and chemically synthesized cellulose fibers (e.g., rayon, cellulose esters (cellulose acetate, etc.), hydroxyalkyl celluloses (e.g., hydroxyethyl cellulose (HEC), hydroxypropyl cellulose, etc.); and alkyl celluloses (methyl cellulose, ethyl cellulose, etc.) and other cellulose ether derivatives). These cellulose nanofibers may be used alone or in combination of two or more kinds.

[0048] Among the above-mentioned cellulose nanofibers, cellulose fibers derived from higher plants, for example, cellulose fibers derived from pulp such as wood fibers (such as wood pulp from conifers, broad-leaved trees, etc.) and seed hair fibers (such as cotton linter pulp), are preferred because they are easy to produce cellulose nanofibers having an appropriate aspect ratio.

[0049] The average diameter of the cellulose nanofibers may be 2 nm to 50 nm, specifically 2.5 nm to 25 nm, and more specifically 3 nm to 5 nm. When the above range is satisfied, the cellulose nanofibers can be uniformly dispersed in the negative electrode active material layer, and thus the conductivity of the negative electrode, the adhesive strength of the negative electrode, and the life characteristics of the battery can be further improved. The average diameter refers to the average value of the diameters of the top 10 cellulose nanofibers and the bottom 10 cellulose nanofibers when the negative electrode active material layer of the manufactured negative electrode is observed at a magnification of several tens of thousands (e.g., 10,000 times) using a TEM.

[0050] The average length of the cellulose nanofibers may be 0.3 μm to 20 μm, specifically 0.5 μm to 10 μm, and more specifically 1 μm to 5 μm. When the range is satisfied, the cellulose nanofibers can be uniformly dispersed in the negative electrode active material layer, and thus the conductivity of the negative electrode, the adhesive strength of the negative electrode, and the life characteristics of the battery can be further improved. The average length refers to the average value of the lengths of the top 10 cellulose nanofibers and the bottom 10 cellulose nanofibers when the negative electrode active material layer of the manufactured negative electrode is observed at a magnification of several tens of thousands (e.g., 10,000 times) using a TEM.

[0051] The average aspect ratio of the cellulose nanofibers may be 30 to 2,000, specifically 50 to 1,000, and more specifically 300 to 500. When the above range is satisfied, the cellulose nanofibers can be uniformly dispersed in the negative electrode active material layer, and thus the electrical conductivity of the negative electrode, the adhesive strength of the negative electrode, and the life characteristics of the battery can be further improved. Here, the aspect ratio means the length relative to the diameter of the cellulose nanofibers. The average aspect ratio means the average value of the aspect ratios of the top 10 cellulose nanofibers and the bottom 10 cellulose nanofibers when the negative electrode active material layer of the manufactured negative electrode is observed at a magnification of several tens of thousands (for example, 10,000 times) by TEM.

[0052] The cellulose nanofibers may be contained in the negative electrode active material layer at 0.1 wt% to 3 wt%, specifically 0.2 wt% to 1.5 wt%, more specifically 0.4 wt% to 1.0 wt%, for example 0.5 wt% to 1.0 wt%. When the above range is satisfied, the tensile strength of the binder is effectively improved, and the life characteristics of the battery can be further improved.

[0053] In the negative electrode active material layer, the weight ratio of the acrylic polymer to the cellulose nanofiber may be 6:4 to 9.8:0.2, specifically 7:3 to 9.8:0.2, more specifically 8:2 to 9.5:0.5, for example 8:2 to 9:1. When the above range is satisfied, the tensile strength (toughness) of the entire binder can be sufficient, so that the detachment of the negative electrode active material is suppressed and the conductive path is secured, and the life of the battery can be improved. In addition, the viscosity of the negative electrode slurry can be maintained at an appropriate level, so that the phase stability of the negative electrode slurry can be improved.

[0054] The negative electrode active material layer may further include a conductive material. The conductive material is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and may be, for example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fiber such as carbon fiber or metal fiber; conductive tube such as single-walled carbon nanotube, double-walled carbon nanotube, or multi-walled carbon nanotube; fluorocarbon; metal powder such as aluminum powder or nickel powder; conductive whisker such as zinc oxide or potassium titanate; conductive metal oxide such as titanium oxide; or conductive material such as polyphenylene derivative. The conductive material may be contained in the negative electrode active material layer in an amount of 5% by weight to 10% by weight, specifically 5% by weight to 15% by weight.

[0055] <Secondary battery> A secondary battery according to another embodiment of the present invention may include the negative electrode of the above-mentioned embodiment. Specifically, the secondary battery may include the negative electrode of the above-mentioned embodiment, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the negative electrode described above. The negative electrode has been described above, so a detailed description thereof will be omitted.

[0056] The positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material. In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may generally have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0057] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+a M b O 2+c may include:

[0058] More specifically, the positive electrode active material is Li 1+a M b O 2+ccomprising, M may be at least one element selected from the group consisting of Ni, Co, Mn, Fe, P, Al, Mg, Ca, Zr, Zn, Ti, Ru, Nb, W, B, Si, Na, K, Mo, and V, and -0.2 ≦ a ≦ 0.2, 0 < b ≦ 2, 0 ≦ c ≦ 2 may hold. Preferably, the a may satisfy -0.1 ≦ a ≦ 0.1, more preferably 0 ≦ a ≦ 0.1. Specifically, the Li 1+a M b O 2+c is Li 1+a [Ni p Co q M 1 r M 2 s O2 or may be the Li 1+a [Ni p Co q M 1 r M 2 s O2. In the Li 1+a [Ni p Co q M 1 r M 2 s O2, the M 1 may be at least one element of Al and Mn, M 2 may be at least one element selected from the group consisting of Fe, P, Mg, Ca, Zr, Zn, Ti, Ru, Nb, W, B, Si, Na, K, Mo, and V, the p may satisfy 0 < p < 1, preferably 0.3 < p < 1, more preferably 0.5 < p < 1, the q may satisfy 0 < q < 1, preferably 0 < q < 0.7, more preferably 0 < q < 0.5, the r may satisfy 0 < r < 1, preferably 0 < r < 0.7, more preferably 0 < r < 0.5, and the s may satisfy 0 ≦ s ≦ 0.2, preferably 0 ≦ s ≦ 0.1. The Li 1+a M b O 2+c is LiCoO2, LiNiO2, LiMnO2, Li[Ni 0.5 Co 0.3 Mn 0.2 O2, Li[Ni0.6 Co 0.2 Mn 0.2 ]O2, Li[Ni 0.7 Co 0.1 Mn 0.2 ]O2, Li[Ni 0.8 Co 0.1 Mn 0.1 ]O2, Li[Ni 0.9 Co 0.05 Mn 0.05 ]O2, LiMn2O4, LiFePO4, 0.5Li2MnO3·0.5Li[Mn 0.4 Ni 0.3 Co 0.3 ]O2. Preferably, the Li 1+a M b O 2+c is Li[Ni 0.6 Co 0.2 Mn 0.2 ]O2, Li[Ni 0.7 Co 0.1 Mn 0.2 ]O2, Li[Ni 0.8 Co 0.1 Mn 0.1 ]O2, Li[Ni 0.9 Co 0.05 Mn 0.05 ]O2. The positive electrode active material may be contained in the positive electrode active material layer at 95% by weight to 99% by weight. When the positive electrode is used in combination with the negative electrode of the above-mentioned embodiment, it is possible to prevent an overpotential from occurring in the positive electrode.

[0059] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the above-mentioned positive electrode active material. In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause chemical changes in the battery that is constructed and has electronic conductivity.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one of these may be used alone or a mixture of two or more of them may be used.

[0060] In addition, the positive electrode binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector.Specific examples of the positive electrode binder include polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination.

[0061] The separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is normally used as a separator in a secondary battery can be used without any particular restrictions, and is preferably low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof may be used. In addition, a normal porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be selectively used as a single layer or multilayer structure.

[0062] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.

[0063] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt. Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0064] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, can be preferably used as high-viscosity organic solvents, because they have a high dielectric constant and dissociate lithium salts well. When such cyclic carbonates are mixed in an appropriate ratio with linear carbonates having low viscosity and low dielectric constant, such as dimethyl carbonate and diethyl carbonate, an electrolyte having high electrical conductivity can be prepared, and therefore such a mixture can be used even more preferably.

[0065] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte solution. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - One or more selected from the group consisting of may be used.

[0066] In addition to the components of the electrolyte, the electrolyte may further include one or more additives such as a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dye, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, or aluminum trichloride, in order to improve the life characteristics of the battery, suppress a decrease in the battery capacity, and improve the discharge capacity of the battery.

[0067] According to another embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics, and high cycle characteristics, and therefore can be used as a power source for medium to large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0068] Below, preferred examples are presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present description, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of the present description. It goes without saying that such changes and modifications fall within the scope of the appended claims.

[0069] Examples and Comparative Examples An acrylic polymer and cellulose nanofibers were prepared as follows.

[0070] (A) Acrylic polymer (A-1) An acrylic polymer (T) produced using 60 parts by weight of acrylamide, 30 parts by weight of acrylic acid, and 10 parts by weight of acrylonitrile g : 120℃, Elastic modulus: 7.99GPa) (A-2) Acrylic polymer (T) produced using 80 parts by weight of acrylamide, 15 parts by weight of acrylic acid, and 5 parts by weight of acrylonitrile g : 110℃, Elastic modulus: 3.12GPa)

[0071] (B) Cellulose nanofiber (B-1) Single-filament cellulose nanofiber (B-2) Molecular fiber-like cellulose nanofiber

[0072] Example 1: Preparation of negative electrode Average particle size (D 50 A negative electrode slurry was produced containing: silicon particles having a size of 5 μm; a conductive material containing carbon black and single-walled carbon nanotubes; an acrylic polymer (A-1); cellulose nanofibers (B-1); and water.

[0073] A copper (Cu) metal thin film with a thickness of 20 μm is applied to both sides of the negative electrode current collector at 150 mg / 25 cm. 2The negative electrode slurry was coated and dried by loading at 100° C. At this time, the temperature of the circulating air was 70° C. Then, the negative electrode current collector coated with the slurry and dried was roll pressed and dried in a vacuum oven at 130° C. for 8 hours to prepare a negative electrode including a negative electrode active material layer. The weight ratio of the silicon particles, the conductive material, the acrylic polymer (A-1), and the cellulose nanofibers (B-1) was 80:10:9.8:0.2.

[0074] Examples 2 to 6 and Comparative Example 1: Production of negative electrodes A negative electrode was prepared in the same manner as in Example 1, except that the conditions were changed as shown in Table 1 below.

[0075] [Table 1]

[0076] Comparative Example 2: Production of negative electrode A negative electrode was produced in the same manner as in Example 1, except that styrene-butadiene rubber and carboxymethyl cellulose were used instead of the acrylic polymer (A-1) and the cellulose nanofibers (B-1). The weight ratio of the silicon particles, conductive material, styrene butadiene rubber, and carboxymethyl cellulose was 80:10:3:7.

[0077] [Table 2]

[0078] The average diameter means an average value of diameters of the top 10 cellulose nanofibers having the largest diameter and the bottom 10 cellulose nanofibers having the smallest diameter when the negative electrode active material layer of the manufactured negative electrode is observed by TEM at 10,000 times magnification, and the average length means an average value of lengths of the top 10 cellulose nanofibers having the largest diameter and the bottom 10 cellulose nanofibers having the smallest diameter when the negative electrode active material layer of the manufactured negative electrode is observed by TEM at 10,000 times magnification.

[0079] The average aspect ratio means the average value of the aspect ratios of the top 10 cellulose nanofibers and the bottom 10 cellulose nanofibers when the negative electrode active material layer of the manufactured negative electrode is observed at 10,000 magnifications using a TEM.

[0080] Experimental example 1: Evaluation of life characteristics (capacity retention rate) Secondary batteries were produced using the negative electrodes of Examples 1 to 6 and Comparative Examples 1 and 2, respectively.

[0081] As a positive electrode active material, Li[Ni 0.9 Mn 0.05 Co 0.05 The positive electrode active material, multi-walled carbon nanotubes (MWCNT) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were mixed in a weight ratio of 96:2:2 in N-methyl-2-pyrrolidone solvent to prepare a positive electrode slurry.

[0082] The prepared positive electrode slurry was applied to an aluminum metal thin film, which was a positive electrode current collector, having a thickness of 15 μm, and dried. At this time, the temperature of the circulating air was 110° C. Then, the positive electrode slurry was rolled and dried in a vacuum oven at 130° C. for 2 hours to form a positive electrode active material layer.

[0083] The negative electrode, the positive electrode, and the porous polyethylene separator were assembled using a winding method. An electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC) = 1 / 2 (volume ratio) and lithium hexafluorophosphate (LiPF61 mol) was injected into the assembled battery to manufacture a lithium secondary battery.

[0084] The secondary battery was charged and discharged to evaluate its life characteristics (capacity retention rate). The battery was charged and discharged at 0.1 C for the first and second cycles, and at 0.5 C for the third to 100th cycles.

[0085] Charging conditions: CC (constant current) / CV (constant voltage) (5mV / 0.005C current cut-off) Discharge condition: CC (constant current) condition 1.5V The capacity retention rates were calculated as follows. Capacity retention rate (%) = (200th discharge capacity / 1st discharge capacity) x 100

[0086] [Table 3]

[0087] 1, the capacity retention rates of the secondary batteries using the negative electrodes of Examples 1 to 6 in which an acrylic polymer and cellulose nanofibers were used in combination are greater than the capacity retention rate of the secondary battery using the negative electrode of Comparative Example 1 in which only the acrylic polymer was used, and are greater than the capacity retention rate of the secondary battery using the negative electrode of Comparative Example 2 in which styrene-butadiene rubber and carboxymethyl cellulose were used. In addition, when Example 4 and Example 5 are compared, it is found that Example 5, which uses an acrylic polymer in which acrylamide is used in an amount of 80 parts by weight based on 100 parts by weight of the monomer mixture, has a higher capacity retention rate than Example 4, which uses an acrylic polymer in which acrylamide is used in an amount of 60 parts by weight based on 100 parts by weight of the monomer mixture.

[0088] Moreover, it can be seen that Example 5, in which cellulose nanofibers with an aspect ratio of 400 are present in the negative electrode active material layer, has a higher capacity retention rate than Example 6, in which the aspect ratio is 85.

Claims

1. A negative electrode active material layer is included, the negative electrode active material layer includes a negative electrode active material and a binder, The binder is a) an acrylic polymer which is a polymer of a monomer mixture containing a (meth)acrylamide group-containing monomer, an unsaturated carboxylic acid monomer, and a monomer having a solubility in water of 100 g / L or less; b) cellulose nanofibers; and a negative electrode.

2. 2. The negative electrode according to claim 1, wherein the (meth)acrylamide group-containing monomer is included in an amount of 60 to 90 parts by weight based on 100 parts by weight of the polymer of the monomer mixture.

3. 2. The negative electrode of claim 1, wherein the (meth)acrylamide is acrylamide.

4. 2. The negative electrode according to claim 1, wherein the unsaturated carboxylic acid monomer is included in an amount of 8 to 30 parts by weight based on 100 parts by weight of the polymer of the monomer mixture.

5. The negative electrode according to claim 1 , wherein the unsaturated carboxylic acid monomer is acrylic acid.

6. 2. The negative electrode according to claim 1, wherein the monomer having a solubility in water of 100 g / L or less is included in an amount of 2 to 10 parts by weight based on 100 parts by weight of the polymer of the monomer mixture.

7. 2. The negative electrode according to claim 1, wherein the monomer having a solubility in water of 100 g / L or less is acrylonitrile.

8. The glass transition temperature (T g 2. The negative electrode of claim 1, wherein the temperature is 100° C. to 150° C.

9. 2. The negative electrode according to claim 1, wherein the acrylic polymer is contained in the negative electrode active material layer in an amount of 1% by weight to 30% by weight.

10. The negative electrode according to claim 1, wherein the cellulose nanofibers have an average diameter of 2 nm to 50 nm.

11. The negative electrode according to claim 1, wherein the cellulose nanofibers have an average length of 0.3 μm to 20 μm.

12. The negative electrode according to claim 1, wherein the cellulose nanofibers have an average aspect ratio of 30 to 2,000.

13. The negative electrode according to claim 1, wherein the cellulose nanofibers are contained in the negative electrode active material layer in an amount of 0.1% by weight to 3% by weight.

14. In the negative electrode active material layer, The negative electrode according to claim 1, wherein a weight ratio of the acrylic polymer to the cellulose nanofibers is 6:4 to 9.8:0.

2.

15. 10. The anode of claim 1, wherein the anode active material comprises silicon particles.

16. A secondary battery comprising the negative electrode according to claim 1.

Citation Information

Patent Citations

  • Binder composition for silicon-based negative electrode of lithium ion secondary battery, and slurry composition for silicon-based negative electrode of lithium ion secondary battery

    JP2016181422A

  • Slurry for electrode, electrode and manufacturing method thereof, and secondary battery

    JP2018116818A

  • Composite particle for electrochemical element electrode

    WO2015098632A1

  • Slurry composition for secondary battery negative electrode, dispersant composition for secondary battery negative electrode slurry, negative electrode for secondary battery, and secondary battery

    WO2020066734A1

  • Binder for lithium secondary battery negative electrode, and lithium secondary battery negative electrode including same

    WO2021060737A1

Cited By

  • Power storage device and electrode active material

    WO2026163607A1

  • Electrode mixture and power storage device

    WO2026163677A1